ANALISIS PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANG PADA CV. PURWA DAYA SEJAHTERA PALEMBANG - Rizal Effendi; Yancik Syafitri (Universitas Tridinanti, 2022)
One form of company is a trading company, namely a company that carries out its business activities by buying products from producers and or other companies to then resell them to the public and consumers. One of the most important elements in a trading company is inventory. This planning activity is not an easy thing to do because in the planning it must be determined the right amount of merchandise to be sold must be in accordance with consumer tastes and must be provided at the right time. For this reason, internal control over inventory will greatly help the company prevent errors in inventory handling. This is very much supported by the company's accounting information system, especially the function of recording and evaluating inventory. If the procedures for recording and valuing inventories from beginning to end have been carried out correctly, the summation in the financial statements will be good and correct as well. Another reason that supports the importance of planning and controlling.Keywords: Planning and Controlling